2012 International Conference on E-Learning and E-Technologies in Education (ICEEE) 2012
DOI: 10.1109/icelete.2012.6333404
|View full text |Cite
|
Sign up to set email alerts
|

Arab preschoolers, interactive media and early literacy development

Abstract: This paper discusses the causes, extent and implications of the digital language divide in technologies used by young Arabic-speaking children by the example of Egyptian preschoolers. The discussion is based on two studies: A preliminary survey examining the nature of Egyptian preschoolers' use of technology and an analytical evaluation of representative Arabic literacy developing applications available for Egyptian children compared to their English counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
2
2
0
2
Order By: Relevance
“…In particular, the analysis of some studies revealed that parents of younger children tend to hold more negative attitudes and adopt more mediation strategies. These ideas are consistent with a number of studies in the literature (Dong et al, 2021; Shoukry et al, 2012) which highlighted that parents adopt more mediation strategies, including more supervision and restriction, to protect their younger children from the potential and perceived harms of digital technologies. Further, studies in countries such as Turkey, Spain, the United Kingdom, and Canada demonstrated that parents have diverse attitudes towards using digital technologies in the home context (Ozturk & Ohi, 2018, 2019; Poveda et al, 2020; Teichert, 2020a).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In particular, the analysis of some studies revealed that parents of younger children tend to hold more negative attitudes and adopt more mediation strategies. These ideas are consistent with a number of studies in the literature (Dong et al, 2021; Shoukry et al, 2012) which highlighted that parents adopt more mediation strategies, including more supervision and restriction, to protect their younger children from the potential and perceived harms of digital technologies. Further, studies in countries such as Turkey, Spain, the United Kingdom, and Canada demonstrated that parents have diverse attitudes towards using digital technologies in the home context (Ozturk & Ohi, 2018, 2019; Poveda et al, 2020; Teichert, 2020a).…”
Section: Discussionsupporting
confidence: 87%
“…For instance, Neumann (2018) highlighted the crucial role parental scaffolding can play in improving the digital literacy practices of children who were using tablets at home in Australia. The findings of the present narrative review showed that parents have used more scaffolding in the home context to support their children's digital literacy practices in recent years (Flewitt & Clark, 2020;Kumpulainen et al, 2020) compared to 11 years ago where parents mostly used a restrictive mediation strategy (Shoukry et al, 2012). Further, from 2015 to 2021, mobile digital technologies gained more momentum in the home context which has resulted in the change of parental mediation strategies.…”
Section: The Impact Of Family Ses Parental Attitudes and Mediation St...mentioning
confidence: 72%
“…In this study, preschoolers' preferences for listening to educational songs via YouTube corroborated Shoukry et al's [35] study. e use of the resources was ordered number 2 as they attracted the preschoolers to learn the alphabet.…”
Section: "As For the Technique Used To Introduce Letters We Researche...supporting
confidence: 88%
“…Kemampuan membaca merupakan pemahaman anak terkait dengan simbol, bunyi, kosakata, kalimat dalam bentuk cetak yang diproses dengan kemampuan kognitif yang dimilikinya agar mendapatkan informasi (Niklas, Cohrssen, & Tayler, 2016). Membaca merupakan proses yang panjang dan rumit yang melibatkan keterampilan kognitif berbeda dan dimulai pada awal perkembangan anak (Sturm, Galal-edeen, & Shoukry, 2012). Beberapa literatur telah membahas topik tentang anak yang harus bisa membaca telah menjadi masalah universal (Al-barakat & Bataineh, 2011).…”
Section: Pendahuluanunclassified